2011
DOI: 10.35800/jpkt.7.3.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

KUALITAS AIR PADA KOLAM LOBSTER AIR TAWAR (Cherax quadricarinatus) DI BBAT TATELU

Abstract: The study was done at the culture site and in the laboratory. The former covered water temperature and pH in the spawning, nursery and rearing ponds, in the morning, 06:00-07:00, at noon,12:00-13.00, and in the afternoon 17:00 to 18:00. Measurements were taken for 2 weeks. The latter included Dissolved Oxygen (DO), Ammonia, Nitrite, Carbon Dioxide (CO2) and turbidity. Water samples were analyzed in the Laboratory of Freshwater Aquaculture Center (BBAT) Tatelu, North Minahasa. Results showed that water temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
2
0
5
Order By: Relevance
“…The monitoring and stabilizing sea water in the lobster tank determine from it. The optimal quality of sea water for lobster is 25o C to 27o C with 25 to 30 ppt of salinity and 7,4 to 8,3 PH, This is in accordance with the ideal range of sea water conditions for lobster [11]. Refer to this study, we use it to get the threshold number of sea water quality changes and stabilize it to get the optimal sea water quality.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The monitoring and stabilizing sea water in the lobster tank determine from it. The optimal quality of sea water for lobster is 25o C to 27o C with 25 to 30 ppt of salinity and 7,4 to 8,3 PH, This is in accordance with the ideal range of sea water conditions for lobster [11]. Refer to this study, we use it to get the threshold number of sea water quality changes and stabilize it to get the optimal sea water quality.…”
Section: Resultssupporting
confidence: 66%
“…Based on the results of the two tables above it can be concluded that the experimental results with Standard Measuring Instruments are successful because the difference in results is not too far away and it can be said that the accuracy of prototypes is approximately 90%. The results showed that air temperature, pH, DO, CO2, turbidity, ammonia and nitrite were in the range suitable for lobster cultivation [11].…”
Section: Resultsmentioning
confidence: 96%
“…Berdasarkan Tabel 2 parameter kualitas air yang tidak sesuai dengan baku mutu air nasional untuk sungai serta danau dan sejenisnya kategori kelas 2 dan 3 untuk peruntukkan pembudidayaan ikan air tawar ini meliputi nitrit, fosfat dan BOD. Konsentrasi nitrit yang diperoleh ini jauh lebih tinggi dibandingkan dengan kolam BBAT Tatelu (Tumembouw, 2011) dan lebih tinggi sekitar 0 -20 dibandingkan dengan perairan estuari seperti Teluk Banten (Alianto et al, 2008). Tingginya konsentrasi nitrit sebagai indikator sedang berlangsung atau sebagai bentuk transisi dari dekomposisi amonia ke nitrat (Effendi, 2003).…”
Section: Hasil Dan Pembahasanunclassified
“…Apabila pH air < 4,8 maka ikan banyak yang mati, karena pada pH terlalu rendah akan banyak mengandung H + terlarut dan amonia (NH4 + ) yang tinggi (Rahayu, 2019). Keberadaan amonia tersebut akan berikatan dengan gas CO2 atau karbondioksida di dalam air, sehingga menjadi racun yang sebagian besar berasal dari hasil sisa metabolisme ikan maupun biota lainnya (Tumembouw, 2011).…”
Section: Metodeunclassified